Strengthening Blue Economy Policy to Achieve Sustainable Fisheries - Sapriani, Sapriani; Kusumaningtyas, Reza Octavia; Elfaki, Khalid Eltayeb (Lembaga Contrarius Indonesia, 2024)
Particularly in developing nations, the aquaculture and fisheries sector is vital to the nutrition and food security of the global population. Nevertheless, notwithstanding their substantial social and economic potential, fishery resources are susceptible to overexploitation and hurting the environment. This research assesses the significance of bolstering blue economy policies to enhance sustainable maritime policies. This study employs the methodology of normative legal research. The research findings, the deterioration of ecological equilibrium, as evidenced by the diminishing carrying capacity of the sea, can be attributed to conservation efforts that lack a stronger emphasis on sustainable management. Maintaining the fundamental tenets of equitable and sustainable fisheries management in nations endowed with oceans is paramount. State and government policies toward society and distributive equity are inextricably linked in managing fisheries resources; local governments may be entrusted with autonomous design and assistance responsibilities for these policies. As a result, a revised vision for constructing a sustainable, equitable, and ambitious blue economy is proposed. Promoting resource-based economic development in the marine and fisheries industrial sector while preserving coastal environments and marine resources through the blue economy concept is possible. This vision is founded upon the following five governance principles: inclusive and equitable processes, climate stability, sustainable consumption and production, circular processes, and the promotion of healthy ecosystems.